Performance Effectiveness Based on Accounting Information Systems in The Framework of Tourism Villages in Bali - Kadek Goldina Puteri DEWI; I Putu Budi ANGGIRIAWAN (International Journal of Environmental, Sustainability, and Social Science, 2023)
Performance is the level of success of a person as a whole at a certain time in carrying out a task. Performance has the most important role, if performance decreases, it will gradually threaten the company and result in the company going bankrupt. Based on the phenomena and results of previous studies, the accounting information system is a component that can be streamlined to improve performance. Apart from Accounting Information Systems, accounting knowledge is considered very important for the Company. The cultural aspect is an aspect that greatly influences the effectiveness of the implementation of a technology. Technological developments must be followed by the desire of the community to increase their ability to utilize this technology. The population in this study is 238 Tourism Villages obtained from data from the Bali Provincial Tourism Office for 2022. The sample size is determined by calculating using the Slovin Formula and the proportional number of sample members is determined using the Yamane Formula. Based on the results of this study, the variable Accounting Knowledge has no significant effect on performance, both before the moderating variable (organizational culture) and after the moderation variable (organizational culture) and the variable Accounting Information System Effectiveness have a significant positive effect on performance. However, the existence of a moderating variable (organizational culture) shows that the effectiveness of the accounting information system variable has no significant effect on performance